Nonstationary interannual teleconnections modulated by multidecadal variability - López-Parages, Jorge; Villamayor, Julián; Gómara, Iñigo; Losada, Teresa; Martín Rey, Marta; Mohíno, Elsa; Polo, Irene; Rodríguez-Fonseca, Belén; Suárez, Roberto (Física de la Tierra, 2013)
The present work shows observational evidence of changes in atmospheric teleconnections of West Africa (WA) and the Euro-Mediterranean (EM) areas with remote regions. We show that the impact of the tropical Sea Surface Temperature (SST) anomalies over the WA precipitation has changed in the late 1970s, which is relevant for seasonal predictions in this area. These changes coincide with a nonstationary link between the interannual variability of the tropical Atlantic and Pacific basins. Also, the link between the Pacific El Niño and the EM rainfall in late winter-spring has changed throughout the 20th century. Our results give evidence of nonstationarities of both types, atmospheric and oceanic, occurring during negative phase periods of the Atlantic Multidecadal Oscillation (AMO). Hence, the results obtained here point out a physical coherent modulation of interannual variability by multidecadal variability. These multidecadal modes also appear to influence the variability of explosive cyclones (EC) over the EM region. Finally, to further understand the AMO and its possible influence over the interannual variability, the ability to reproduce a coherent AMO in General Circulation Models (GCMs) has been analysed. Results show that both the simulated and observed AMO patterns are consistent.